A short overview of bird control in sweet and sour cherry orchards — Possibilities of protection of bird damage and its effectiveness - Simon, G. (International Journal of Horticultural Science, 2008)
A short overview of bird control in sweet and sour cherry orchards — Possibilities of protection of bird damage and its effectiveness